Geomorphological Properties of Bulanik-Malazgirt Basin (Mus) - Kiransan, Kemal; Sengun, M. Taner (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Bulanik-Malazgirt (Mus) basin is located in Upper Murat-Van section, in the Eastern Anatolian Region of Turkey. The basin is rich in point of geomorphological features. There are geological units of different times in the basin and the basin is close to tectonically mobile areas. Basin have important forms belong to volcanic, structural, fluvial and glacial morphology. Despite all these remarkable features, geomorphological studies on Bulanik-Malazgirt Basin are inadequate in the literature. Purpose of this study, geomorphological features of Bulanik-Malazgirt Basin located in northeastern Turkey and factors affecting the emergence of these features are to define. Data used by geomorphology and research methods with Geographic Information Systems was used in this study. The data of the study are literature, geological and topographic maps, digital elevation model and field study data. As a result, wide variety morphological units such as mountainous areas, plateau areas, canyon valleys, plains and basins, terraces, aluvial fans were formed with effect of lithological, tectonic and climatic characteristics of the Bulanik-Malazgirt Basin. Mount Guzelbaba and Laladag are in the north of the basin, Akdogan Mountains and Bilican Mountain are in the West, Yakupaga Mountains, Ziyaret Mountains and Suphan Mountain are in the South. Cemalverdi Mountain and volcanic plateau field are in the East. Despite research area corresponded a low zone between mountainous fields are basin in terms of geomorphological and geological, hydrographically are not basin.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Bulanik-Malazgirt Basin; Geomorphology; Mus